ANALISIS KANDUNGAN NITRAT, NITRIT, DAN ORTOFOSFAT DI PERAIRAN PULAU MERAK KECIL - Salsabilla, Dewi Firda; Sasongko, Agung Setyo; Cahyadi, Ferry Dwi (Universitas Teuku Umar, 2023)
The city of Cilegon has a variety of marine tourism destinations, one of which is Merak Kecil Island. The waters around Merak Kecil Island are known for offering a beach and sea atmosphere. In addition, visitors can enjoy a number of facilities such as boat tours, fishing, snorkeling, and enjoying the sights of ships passing by. Related to this, it will have the potential to affect the environmental conditions of Merak Kecil Island, especially the fertility of the waters. The fertility of a waters is influenced by nutrients (nitrate, nitrite, phosphate). Nitrate, nitrite and phosphate act as limiting factors for the growth of organisms and water fertility. This study aims to determine the differences in content and the relationship between nitrate, nitrite and phosphate content and compared with Government Regulation no. 22 of 2021 and ANZECC & ARMCANZ (2000). The research method uses a descriptive method with a quantitative approach while the selection of sampling locations uses a purposive sampling method. Required environmental parameters were taken in situ and air samples were analyzed at the Fish and Environmental Health Testing Center (BPKIL) Serang, Banten. The results showed that there were less significant differences in the content of nitrate, nitrite, and phosphate. The nitrate content exceeded the quality standard, but nitrite and phosphate were not detected.